Firm Employment Growth, R&D Expenditures and Exports - Marco Di Cintio; Sucharita Ghosh; Emanuele Grassi (Fondazione Eni Enrico Mattei (FEEM), 2016)
This paper studies firms' decisions to export and invest in R&D and their effects on employment growth and labor flows for a sample of Italian SMEs operating in the manufacturing industry. After accounting for the under-reporting of R&D in SMEs, our quantile regressions reveal that (i) R&D is associated with higher employment growth rates, higher hiring rates and lower separation rates; (ii) R&D-induced exports are negatively related to employment growth and accessions and positively related to separations; and (iii) pure exports are not a driver of employment growth and labor flows.
Keywords: J63; M51; O31; F14; 330; Exports; R&D; Firm Growth; Quantile Regression